Islam Saintifik : Langit Bertabur Ayat, Bumi Bertabur Fakta. - Andi Ardiansyah; Kurniati . (CV. ITTC INDONESIA, 2025)
This journal article examines the concept of Scientific Islam as an epistemological middle path between Islamic revelation and modern science, emphasizing a harmonious integration of faith, reason, and empirical observation without a detrimental dichotomy. The study employs an integrative methodology that combines philosophical, historical, and empirical analyses. The proposed approach adopts a practical model in which revelation is understood not only as a source of moral inspiration but also as a source of theoretical hypotheses in scientific research. This is exemplified in biotechnology studies that incorporate metaphysical dimensions to prevent human exploitation and safeguard human dignity.Within the historical development of Islamic civilization, the article outlines the periodization of the Golden Age (seventh to fourteenth centuries) under the Abbasid, Umayyad, and Fatimid dynasties. Cities such as Baghdad particularly through the Bayt al-Hikmah as a major center for translating Greek, Persian, and Indian works into Arabic emerged as epicenters of global innovation. This era was characterized by major advances in mathematics (Al-Khwarizmi’s development of algebra and algorithms, which significantly influenced European mathematics), medicine (Ibn Sina’s Al-Qanun fi al-Tibb, which remained a standard medical reference until the seventeenth century), astronomy (Al-Battani’s refinement of Ptolemaic tables), philosophy (Al-Farabi as the “Second Teacher” after Aristotle), and architecture (such as the Great Mosque of Cordoba and Al-Haram, reflecting the integration of art and science). These contributions not only preserved ancient knowledge but also produced original discoveries, including the development of the decimal number system and the concept of zero, initially derived from India and further developed by Muslim scholars. Trade networks along the Silk Road and the Mediterranean facilitated cross-cultural dialogue, positioning Islam as an intellectual bridge between East and West and significantly influencing the European Renaissance for example, the incorporation of Al-Razi’s works on pharmacology into European universities.